THE MODEL OF TAX EVASION, ITS COHERENCE TO THE PRACTICAL TAX ADMINISTRATION - Anciūtė, Aurelija; Kropienė, Rūta (Ekonomika, 2010)
In this paper, a theoretical model of tax evasion, proposed by Allingham and Sandmo, is briefly presented. This model tries to explain the taxpayer’s decision to reveal only part of the taxable income and to evade taxes in this way. The main parameters of the model are personal income, the rates of tax and penalty, probability of the tax audit. By the method of comparative statics it is possible, at least partially, to evaluate the influence of changes of the model’s parameters on a person’s decision to evade tax.As some of the assumptions of the Allingam–Sandmo model differ from taxation rules in practice or the model’s conclusions do not match the actual taxpayers’ behaviour, in this paper some criticism and improvements of the proposed model are reviewed. A comparison of the model’s assumptions and actual aspects of the tax administration in Lithuania is also provided.This article contains also a model of tax evasion with regard for the peculiarities of tax administration in Lithuania and the possible corrections of tax audit probability function.